COMPREHENSIVE ANALYSIS OF LABORATORY AUTOMATION TECHNOLOGIES AND EVALUATING EFFICIENCY, ACCURACY, AND COST-EFFECTIVENESS IN CLINICAL LABORATORY OPERATIONS - Mohammed Al Hassan Al Malki, ‏Saad Abdullah Mohammad Alqarni, ‏Turki Abdulrahman Alowaidi, Ahmad Saad Alqarni, Abdulellah Mansor Al Enami, ‏Ali Hebni Alshehri, Waleed Atyah Alzahrani, ‏Abdulaziz Ali Abdulaziz Alasmri (Chelonian Research Foundation, 2022)
Automated solutions changed the scientific aspect of clinical laboratories by mostly simplifying the processes by reducing congestion, improving efficiency, giving much accuracy, and hence decreasing costs. Deep research goes into robotic systems and middleware solutions in laboratories of a wide variety, where laboratory information management systems (LIMS) and robotic systems are studied. Such manufacturing process analysis digs into scientific articles and real-life cases to find how laboratory automation affects workflow speed, quality of work, and, consequently, cost reduction in clinics. Essential liners like workflow optimization and integration abilities with data management and the profitability of automation will be sincerely considered to give a complete picture of the advantages and boundaries of automation in laboratories. With automation technologies leading the way, laboratories will progress by introducing new procedures, bringing more efficiency to the performance of medical care, and eventually, the healthcare centers´ operations will become effective, and the patients will get exemplary services. Keywords: laboratory automation, clinical laboratory, efficiency, accuracy, cost-effectiveness, robotic systems, middleware, laboratory information management systems (LIMS).